Effect of chemical abrasion of zircon on SIMS U–Pb, δ18O, trace element, and LA-ICPMS trace element and Lu–Hf isotopic analyses - C. Kooymans; C. W. Magee Jr.; K. Waltenberg; N. J. Evans; S. Bodorkos; Y. Amelin; Y. Amelin; S. L. Kamo; T. Ireland; T. Ireland (Geochronology, 2024)
This study assesses the effect of chemical abrasion on in situ mass spectrometric isotopic and elemental analyses in zircon. Chemical abrasion improves the U–Pb systematics of SIMS (secondary ion mass spectrometry) analyses of reference zircons, while leaving other isotopic systems largely unchanged. SIMS 206Pb/238U<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="57pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="0e7f0274f6f359dc8ea519812ebbfe44"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="gchron-6-337-2024-ie00001.svg" width="57pt" height="15pt" src="gchron-6-337-2024-ie00001.png"/></svg:svg> ages of chemically abraded reference materials TEMORA-2, 91500, QGNG, and OG1 are precise to within 0.25 % to 0.4 % and are within uncertainty of chemically abraded TIMS (thermal ionization mass spectrometry) reference ages, while SIMS 206Pb/238U<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="57pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="f357d854cd57aae1f270b2d3c0090b15"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="gchron-6-337-2024-ie00002.svg" width="57pt" height="15pt" src="gchron-6-337-2024-ie00002.png"/></svg:svg> ages of untreated zircons are within uncertainty of TIMS reference ages where chemical abrasion was not used. Chemically abraded and untreated zircons appear to cross-calibrate within uncertainty using all but one possible permutation of reference materials, provided that the corresponding chemically abraded or untreated reference age is used for the appropriate material. In the case of reference zircons QGNG and OG1, which are slightly discordant, the SIMS U–Pb ages of chemically abraded and untreated material differ beyond their respective 95 % confidence intervals.